Cervical artificial disc replacement (C-ADR): global perspectives on use and trends - Rhee, John; VanAlstyne, Ellen M; Skelly, Andrea C (Evidence-Based Spine-Care Journal, 2012)
Study design: Cross-sectional survey.Objectives: To obtain information from the global community regarding cervical artificial disc replacement (C-ADR) use and trends before and after US Food and Drug Administration (FDA) approval of devices in 2007 and summarize available information on utilization and government approval for devices. Methods: Data on utilization and approval were sought from PubMed, Google, FDA, and manufacturers’ websites. The 6195 members of AOSpine International were invited to participate in a survey to assess global C-ADR use and trends. Results: Publically available data on utilization, trends, and approval outside of the US and Europe is limited. No studies of utilization were found. Of 1479 professionals responding to the survey, 50% had C-ADR specific training and reported ever performing C-ADR. Most respondents believed that C-ADR was safe and effective, but approximately one quarter responded that they did not know. Of those who had done C-ADR, 49% reported performing ≥ 1 before December compared with 92% after January 2008 and 51.3% indicated that all their C-ADRs were placed in a single level; 27% reported ≥ 1 failures that required revision. The majority foresee that C-ADR use will increase in the next 5 years. Most respondents believed that the best indication is radiculopathy from soft-disc pathology rather than myelopathy or disorders arising from spondylotic (hard-disc) pathology. Conclusion: More C-ADR has been performed after January 2008. Most respondents expect the number to increase. There may be differences in failure rates when performed inside or outside of a sponsored research trial.